Handbook of solid state diffusion. Volume 2, - Paul, Aloke; Divinski, S. V. (Elsevier, 2017)
Handbook of Solid State Diffusion, Volume 2: Diffusion Analysis in Material Applications covers the basic fundamentals, techniques, applications, and latest developments in the area of solid-state diffusion, offering a pedagogical understanding for students, academicians, and development engineers. Both experimental techniques and computational methods find equal importance in the second of this two volume set. Volume 2 covers practical issues on diffusion phenomena in bulk, thin film, and in nanomaterials. Diffusion related problems and analysis of methods in industrial applications, such as electronic industry, high temperature materials, nuclear materials, and superconductor materials are discussed.